ACTING EARLY TO PROTECT RENAL: BEYOND GLYCEMIC CONTROL OF SGLT2 INHIBITORS - Yulianto Kusnadi (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Type 2 Diabetes Mellitus (T2DM) is the leading cause of chronic kidney disease (CKD), accounting for almost half of all cases of kidney failure that necessitate replacement therapy. Cardiovascular disease (CVD) is the leading cause of death in patients with T2DM and CKD. To lower blood glucose levels by inhibiting glucose reabsorption in the proximal tubule, sodium/glucose cotransporter 2 inhibitors (SGLT2-i) were developed. Consistent reductions in risks for secondary kidney disease end points (albuminuria and a composite of serum creatinine doubling or 40% estimated glomerular filtration rate decline, kidney failure, or death) were recognized in clinical trials designed to demonstrate the CVD safety of SGLT2i in type 2 diabetes mellitus (T2DM), as well as reductions in CVD events. The DECLARE-TIMI58 (Dapagliflozin Effect on Cardiovascular Events-Thrombolysis in Myocardial Infarction 58, or DECLARE) trial in patients with T2DM, urinary albumin-creatinine ratio >300 mg/g, and estimated glomerular filtration rate of 30 to 90 mL/min/1.73 m2 established the kidney and CVD benefits of dapagliflozin in patients with CKD. SGLT2i boost glomerular hemodynamic function and are figured to augment other local and systemic processes that contribute to the development of CKD and CVD. According to latest Indonesian Society of Endocrinologist’s guideline, patients with T2DM was recommended to use SGLT2i to reduce their risk of CKD and CVD, in accordance with the clinical trial entry criteria. To achieve widespread use of these life-saving medications, effective implementation strategies are required.